2007
DOI: 10.1352/0895-8017(2007)112[418:eibiof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Early Intensive Behavioral Intervention: Outcomes for Children With Autism and Their Parents After Two Years

Abstract: An intervention group (n ϭ 23) of preschool children with autism was identified on the basis of parent preference for early intensive behavioral intervention and a comparison group (n ϭ 21) identified as receiving treatment as usual. Prospective assessment was undertaken before treatment, after 1 year of treatment, and again after 2 years. Groups did not differ on assessments at baseline but after 2 years, robust differences favoring intensive behavioral intervention were observed on measures of intelligence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
319
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(331 citation statements)
references
References 46 publications
5
319
1
6
Order By: Relevance
“…At present, empirical research clearly supports the use of ABA and other interventions with a behavioral foundation in the treatment of ASD [4]. These results have helped lay the foundation for treatment recommendations prescribed by professional and governmental organizations.…”
Section: Introductionmentioning
confidence: 71%
“…At present, empirical research clearly supports the use of ABA and other interventions with a behavioral foundation in the treatment of ASD [4]. These results have helped lay the foundation for treatment recommendations prescribed by professional and governmental organizations.…”
Section: Introductionmentioning
confidence: 71%
“…Howard, Sparkman, Cohen, Green and Stanislaw (2005) maintain that effective early intervention can produce lasting neurobiological as well as behavioral changes as early experiences play a critical role in shaping brain architecture as well as brain function. Research has indicated in numerous studies that early intensive behavioral intervention is highly effective and much more so than an "eclectic" approach (Remington, Hastings, Kovshoff, Espinosa & Jahr, 2007;Zachor, BenItzchak, Rabinovich & Lahat, 2007;Eikeseth, Smith, Jahr & Eldevik, 2002;Howard et al, 2005). Matson and Smith (2008) maintain that to date enough behaviorally oriented EIBI studies have been conducted to suggest that not only is it effective but as a congregate group of learning based methods, it stands alone as the only effective treatment for young children with ASD.…”
Section: Risk Factors For Challenging Behavior 16mentioning
confidence: 99%
“…Only one child with Autistic Disorder lost the diagnosis by age 9 years, whereas almost half of the children with PDD-NOS lost the diagnosis. Remington et al (2007) also examined a subset of preschool-aged children who achieved a "best outcome" status in their comparison study of EIBI and a treatment-asusual group. The children were evaluated at baseline and then again after 2 years of intervention.…”
Section: Predictors Of Outcome: Child Characteristicsmentioning
confidence: 99%